Acute pancreatitis after thoracic duct ligation for iatrogenic chylothorax. A case report. Issue 1 (December 2017) - Bédat, Benoît; Scarpa, Cosimo; Sadowski, Samira; Triponez, Frédéric; Karenovics, Wolfram
Abstract Background To report the association between thoracic duct ligation and acute pancreatitis. The association between sudden stop of lymphatic flow and pancreatitis has been established in experimental models. Case presentation A 57-year-old woman operated for thymoma presented a iatrogenic chylothorax. After thoracic duct ligation, she presented an acute pancreatitis which resolved after conservative treatment. The chylothorax disappeared within 4 days of thoracic duct ligation. Conclusions This is the first report of acute pancreatitis following thoracic duct ligation. The pancreas and digestive tract should be assessed in symptomatic patients after thoracic duct ligation.